Pengembangan Media Peta Keragaman Budaya Indonesia untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS Kelas IV MI Mathla’ul Anwar - Rafidah, Farah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research is motivated by the difficulty of students in remembering the material that has been conveyed by the teacher. This is partly due to the limited learning media available. This study aims to develop Indonesian Cultural Diversity Map media on the material of Indonesia Rich in Culture. The method used is the Research and Development method with the ADDIE model, (analysis, design. development, implementation and evaluation) The data collection techniques used are interviews, questionnaire observations, tested with 33 students The results of learning media research get 98.8% from media experts and 95% from material experts the level of effectiveness taken from the response questionnaire gets 87.21%, then gets an assessment of 84.4% from the class teacher. Meanwhile, to measure the increase in Learning Outcomes, it is done with pretest and posttest. Judging from the completeness of student learning, the N Gain value is 0.78, which shows an increase in learning outcomes and the Indonesia Cultural Diversity Map media is feasible to use as a learning media and is able to improve student learning outcomes.